Immunostimulatory effects of asiatic acid and madecassoside on the phagocytosis activities of macrophages cell line (J774A.1) - Nurul Hikmah Harun, Wan Amir Nizam Wan Ahmad, Rapeah Suppian (Journal of Applied Pharmaceutical Science, 2021)
Macrophages play a vital role in primary immune responses mainly by carrying out phagocytosis that involves the production of nitric oxide (NO). NO is synthesized by inducible nitric oxide synthase (iNOS) to combat aetiological agents that are able to cause infectious diseases (IDs). Asiatic acid (AA) and madecassoside (MA) are two pentacyclic triterpene compounds derived from Centella asiatica (Linn.) Urban that involved in many pharmacological activities of this plant. However, there is still limited study using a normal immune model that resembles a healthy community to test the immunomodulatory effect of these compounds. Thus, this study used unstimulated macrophages as an in vitro normal model to investigate the effect of both compounds on phagocytosis activity. To achieve the aim of this study, the effects of AA and MA, alone and in combination, on the phagocytosis uptake, NO production, and iNOS expression of macrophages after 24 hours of treatment were measured. Briefly, macrophages (J774A.1) were cultured in five groups, namely untreated macrophages, macrophages treated with lipopolysaccharides (LPS) as a positive control, and macrophages treated with AA and MA alone and in combination (AA + MA). The investigation on phagocytosis uptake, NO production, and iNOS expression were conducted by using microscopic analysis on Giemsa-stained slides, the Griess assay, and Western blot, respectively. The results presented that the combination (AA + MA) treatment enhanced phagocytosis uptake, NO production, and iNOS expression of macrophages when compared to the untreated macrophages as well as macrophages treated with AA and MA, respectively. In conclusion, the combination (AA + MA) treatment is able to stimulate phagocytosis activity of macrophages and this new finding provides initial knowledge for the development of a natural product-based preventive agent against IDs.
Keywords: Asiatic acid, madecassoside, phagocytosis, nitric oxide, iNOS, macrophage J774A.1.